Resiliensi Keluarga dalam Islam - Evie syalviana; Ririn Musdalifah; Syahrul Syahrul (LPPM IAIN Sorong, 2022)
The current phenomenon of sexual violence cannot be denied giving special attention in various sectors. Cases of sexual violence that often occur in the West Papua region itself has become a concern for the community. Family resilience is certainly very important to be implemented and considered as an effort to prevent and protect sexual violence against women and children. The purpose of this article is to find out the form of family resilience as a preventive and protection effort from acts of sexual violence in the Papua region. The research methodology used is descriptive qualitative method. The results showed that there were three forms of family resilience, namely physical resilience, social and religious resilience, and psychological resilience. Papua is known for its traditional religion and culture. In solving every problem, it is also inseparable from the involvement of customary rules, so there is a need for views and strategies for family resilience that are related to the customary rules themselves. Therefore, the 3 components described by the researcher in this article are considered important as a form of family resilience, so as to prevent and protect families, especially women and children, from sexual violence